Unveil of the role of fungal taxa in iron(III) reduction in paddy soil - Li, Ming-Jun; Ye, Xiao-Xin; Da, Yan-Mei; Sun, Qing-Ye; Zhou, Guo-Wei (Frontiers in Microbiology, 2024)
Hitherto, research on iron(III)-reduction has mainly focused on bacteria rather than fungal communities. To acquire insight into fungi involving in iron(III) reduction, typical organic matters (containing cellulose, glucose, lactate and acetate) and ferrihydrite were used as electron donors and acceptor, respectively, in the presence of antibiotics. After antibiotic addition, microbial iron(III) reduction was still detected with quite high rates. In comparison, rates of iron(III) reduction were significantly lower in cellulose-amended groups than those with glucose, lactate and acetate under the antibiotic-added condition. Patterns of intermediate (e.g. acetate, pyruvate, glucose) turnover were markedly different between treatments with and without antibiotics during organic degradation. A total of 20 genera of potential respiratory and fermentative iron(III)-reducing fungi were discovered based on ITS sequencing and genome annotation. This study provided an insight into the diversity of iron(III)-reducing fungi, indicating underestimated contribution of fungi to iron and the coupled carbon biogeochemical cycling in environments.